Tubular Adenoma Pyloric-Gland Type in a Cow - Tostes, Raimundo A.; Voitena, Jessica; Cheng, Arthur C.; Viott, Aline M. (Brazilian Journal of Veterinary Pathology, 2020)
The paper describes a typical Pyloric-Gland Type Tubular Adenoma founded in a 7 years old holstein cow. At necropsy, macroscopic examination showed a pedunculated polypoid formation measuring 4.0 cm in its largest diameter in the mucous membrane of the gallbladder’s body region, with a delicate base in the form of a rod measuring 2.5 cm in length. Histologically analysis showed a tubular cell proliferation covered with cylindrical epithelium, which secreted mucus, with regular, vesicular nuclei with small and regular nucleoli. The stroma was represented by a delicate and loosened, vascularized connective tissue and edema. In the veterinary literature, there is no mention of the occurrence of Pyloric-Gland Type Tubular Adenoma in cattle as well a published description about it.